Nationalism in winter sports judging and its lessons for organizational decision making - Zitzewitz, E. (Journal of Economics & Management Strategy, 2006)
This paper exploits nationalistic biases in Olympic winter sports judging to study the problem of designing a decision-making process that uses the input of potentially biased agents. Judges score athletes from their own countries higher than other judges do, and they appear to vary their biases strategically in response to the stakes, the scrutiny given the event, and the degree of subjectivity of the performance aspect being scored. Ski jumping judges display a taste for fairness in that they compensate for the nationalistic biases of other panel members, while figure skating judges appear to engage in vote trading and bloc judging. Career concerns create incentives for judges: biased judges are less likely to be chosen to judge the Olympics in ski jumping but more likely in figure skating; this is consistent with judges being chosen centrally in ski jumping and by national federations in figure skating. The sports truncate extreme scores to different degrees; both ski jumping and, especially, figure skating are shown to truncate too aggressively. Extreme truncation not only discards information, but may also make the vote trading in figure skating easier to implement. These findings have implications for both the current proposals for reforming the judging of figure skating and for designing decision making in organizations more generally.